2019
DOI: 10.1002/ejoc.201901092
|View full text |Cite
|
Sign up to set email alerts
|

PPh3/Selectfluor‐Mediated Transformation of Carboxylic Acids into Acid Anhydrides and Acyl Fluorides and Its Application in Amide and Ester Synthesis

Abstract: By taking the advantage of PPh3/Selectfluor system, carboxylic acids are efficiently converted into the pivotal intermediates acyloxyphosphonium ions that can selectively react with a second carboxylic acid or fluoride to in situ yield the corresponding acid anhydrides or acyl fluorides. The developed protocol features commercially availabile reagents, no involvement of base, room temperature conditions, and simple experimental procedure. Additionally, various amides or esters are readily achieved, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…In addition, it was found that the inclusion of PPh 3 was the major factor in this switch of reactivity from aminofluorination to diamination. Consistent with this observation, mixing of NFSI and PPh 3 readily generated nucleophilic benzenesulfonimide species (PhSO 2 )­N  and fluorine-trapping products (F 2 PPh 3 and FPPh 3 + ; see the Supporting Information for details) …”
supporting
confidence: 55%
“…In addition, it was found that the inclusion of PPh 3 was the major factor in this switch of reactivity from aminofluorination to diamination. Consistent with this observation, mixing of NFSI and PPh 3 readily generated nucleophilic benzenesulfonimide species (PhSO 2 )­N  and fluorine-trapping products (F 2 PPh 3 and FPPh 3 + ; see the Supporting Information for details) …”
supporting
confidence: 55%
“… 15 , 16 While several synthetic methods for acyl fluorides have been reported, they are typically prepared by using toxic fluorination reagents and/or precious metal catalysts. 17 , 18 Therefore, the development of their different synthetic approach with high practicability is in great demand.…”
Section: Resultsmentioning
confidence: 99%
“…During the second step, the resulting acyloxyphosphonium Tang and co-workers developed a similar synthetic pathway, by using PPh 3 combined with Selectfluor TM instead of NBS and Et 3 N•3HF (Scheme 28). 46 These conditions provided an anhydride as the major product along with trace amounts of the corresponding acyl fluoride. Even though acyl fluorides could generally not be isolated, small amounts were observed after each reaction.…”
Section: Scheme 26 Synthesis Of Acyl Fluorides Using Pph 3 /Nbs and Ementioning
confidence: 99%